INTRODUCTORY NOTES ABOUT THE PLACE OF THE BODY AND ITS INTERFACE BETWEEN GENDER AND SEXUALITY PRESENT IN CURRICULAR COMMON NATIONAL BASE - Souza Monteiro, Solange Aparecida de [UNESP]; Back, Jeizi Loici (Fundacao Univ Tocantins, 2020)
This study analyses the National Common Curricular Base (BNCC), approved in 2018, as a policy that aims to guide the pedagogical work of schools throughout Brazil. Thus, the aim of this study is to analyze how the School, guided by the BNCC, contributes to the standardization of bodies. Methodological guidance as a strategy for data collection, bibliographic and documentary research was used. It was concluded that the School, in capitalist society, tends to form normatized bodies, which attend to well-defined gender roles between men and women, allowing only heterosexuality as an ideal sexual orientation, thus maintaining the exploitation of work and the accumulation of wealth by the bourgeois class.
Keywords: Sexual Education; Gender; Body; Formation; BNCC